Vigilance and control. - Murray, Samuel; Vargas, Manuel (Philosophical Studies, 2020)
We sometimes fail unwittingly to do things that we ought to do. And we are, from time to time, culpable for these unwitting omissions. We provide an outline of a theory of responsibility for unwitting omissions. We emphasize two distinctive ideas: (1) many unwitting omissions can be understood as failures of appropriate vigilance, and; (2) the sort of self-control implicated in these failures of appropriate vigilance is valuable. We argue that the norms that govern vigilance and the value of self-control explain culpability for unwitting omissions.